2017
DOI: 10.1111/jnu.12284
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self‐Management Theory‐Guided Discharge Intervention for Parents of Hospitalized Children

Abstract: Development of a theory-based intervention, the translation of theoretical knowledge to clinical innovation, is an important step toward testing the effectiveness of the theory in guiding clinical practice. Clinical nurses will establish the practice relevance through future use and refinement of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
(44 reference statements)
1
15
0
1
Order By: Relevance
“…Participants were interviewed using Likert‐type and open‐ended questions created by the PI to describe the feasibility (participant burden), acceptability of participating (helpful/unhelpful aspects of the study and intervention), and suggestions for improving the study (Barte, ter Bogt, Beltman, van der Meer, & Bemelmans, ; Oakley et al, ; Sawin et al, ) . The interviews on average were 10–15 min in length.…”
Section: Bsm Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were interviewed using Likert‐type and open‐ended questions created by the PI to describe the feasibility (participant burden), acceptability of participating (helpful/unhelpful aspects of the study and intervention), and suggestions for improving the study (Barte, ter Bogt, Beltman, van der Meer, & Bemelmans, ; Oakley et al, ; Sawin et al, ) . The interviews on average were 10–15 min in length.…”
Section: Bsm Interventionmentioning
confidence: 99%
“…and (3) none of the patterns described normal milk ejection physiology (R. F. Lucas, McGrath, Diallo, & Brandon, 2016 Sawin et al, 2017). The interviews on average were 10-15 min in length.…”
Section: Maternal Assessment Of Infant Breastfeeding Behaviors-revisedmentioning
confidence: 99%
“…The patient and their family needs a care system for health that allows them to meet their own care needs (Mullen et al, 2006). Thus, the method of re-teaching (Sawin et al, 2017) should always be done by the nurse. Brooten et al (2002) demonstrated that the teaching should begin as soon as possible during hospitalisation and frequently repeated to ensure the success of patient learning.…”
Section: Information Dimensionmentioning
confidence: 99%
“…Teach-Back is an educational tool that uses an iterative face-to-face approach when teaching families and asking them to recall, demonstrate or restate what they learned (Kemp et al, 2008;Peter et al, 2015;Ryan and Sawin, 2009). The Teach-back approach was extended to include "think forward", to facilitate the nurse to proactively consider or elicit potential challenges families may encounter after hospital discharge (Sawin et al, 2017). The integration of these frameworks informed the content, as well as the process for this innovative ePED teaching tool that was specifically designed to guide an interactive conversation between the parent and discharging nurse.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The foundation of the app was modeled after research conducted by Sawin et al, (2017) that utilized a longer conversation guide to engage parents at the time of discharge teaching (Sawin et al, 2017). The initial tool included theory-based discharge questions in the form of an iPad app for nurses to use in preparing families for discharge and self-management for their child at home (Sawin et al, 2017).…”
Section: Eped Applicationmentioning
confidence: 99%